CONSUMER INSIGHT UNTUK PERTUMBUHAN USAHA - Bangun, Cicilia Sriliasta (Universitas Esa Unggul, 2021)
The pandemic Covid-19 has affected human behavior and create a new habit called the new normal as a way to survive. Activities that were previously carried out face-to-face must be changed to online. In this kind of condition, sales and marketing team are required to adjust the way of building customer’s communication, listening to voice of customer, finding the insight and introducing the product to the prospectus customer by using the sophisticated technology. Achievement of sales targets is very important for the entrepreneurship growth and business sustainability. The purpose of this online training is to improve the sales and marketing team's skills to understand their customers by collecting consumer insight from many resources included media social which is then outlined in the strategy to achieve sales targets that have been set by the company. Keywords: consumer insight, entrepreneurship growth, social media.